The Effect of Current Ratio and Debt to Equity Ratio on Stock Prices with Return on Equity as an Intervening Variable in Food and Beverage Companies - Christia Christia; Eka Nurmala Sari; Enda Noviyanti Simorangkir; Galumbang Hutagalung (Journal of Social Science, 2021)
This study aims to test and analyze the effect of Current Ratio and Debt to Equity Ratio on stock prices with ROE as an intervening variable . This research is a quantitative research. The population of food and beverage companies is 23 companies using purposive sampling technique, so samples that meet the criteria for analysis are 13 companies. The data were analyzed using multiple linear regression analysis, the cc›efficient of determination, the F test, and the T test. The results showed that the Current Ratio had a positive and significant effect on ROE and stock prices. DER has a positive and significant effect on ROE but has a significant negative effect on stock prices and ROE has a positive and significant effect on stock prices. CR and DER have an indirect effect on stock prices through ROE.